Return and Volatility Spillover among Banks and Insurers: Evidence from Pre-Crisis and Crisis Periods - Elyasiani, Elyas; Kalotychou, Elena; Staikouras, Sotiris K.; Zhao, Gang (My University, 2015)
We investigate the return and volatility interdependencies among the US, the UK, the EU, and Japanese banks and insurers during the period of 2003 to 2009. We find strong return and volatility transmissions within and across banking and insurance industries, strengthened contagious spillover effects during the crisis of 2007 to 2009, and a leading role played by the US financial institutions as information providers in global markets. Furthermore, we find that firm characteristics such as size and leverage drive the interdependencies among major banking firms. Our findings have important implications for effective hedging and diversification strategies, asset pricing and risk management, and the formulation of regulatory and monetary policies.
Keywords: Banks; Spillover; Multivariate GARCH; Crisis; Insurers; Contagion